Total antioxidant activity and enzymatic inhibition against alpha-amylase, alpha-glucosidase and pancreatic lipase of irradiated Archidendron bubalinum - Ja'afar, Nor Liyana; Chai, Pui Teng; Mohd Rosmi, Noor Syafiqa Aqila; Rambli, Siti Nur Atiqah; Shafie, Nurul Husna; Arapoc, Daryl Jesus; Bahari, Hasnah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Archidendron bubalinum is an underutilised plant with numerous antioxidant properties and has a great potential to inhibit enzymes linked with diabetes and obesity. Food irradiation is an advanced technology to prolong the lifespan of plant, prevent physical spoilage and eradicate food borne disease. Present study was aimed to determine the total antioxidant activity, enzymatic inhibition against alpha-amylase, alpha-glucosidase and pancreatic lipase and the toxicity levels of non-irradiated and irradiated (3, 6, 9 & 12 kGy) hot aqueous extract of A. bubalinum. Methods: The antioxidant ability of the extract was determined by total phenolic content (TPC), total flavanoid content (TFC), Diphenyl-1-Picrylhydrazyl (DPPH), β-carotene assay and ferric reducing antioxidant potential (FRAP) assay. The inhibitory activities were evaluated using α-amylase, α-glucosidase, and pancreatic lipase inhibition as-say. The toxicity levels of A. bubalinum extract were determined using Brine shrimp and Zebra-fish assays. Results: Results showed that irradiated A. bubalinum at 12 kGy demonstrated the highest TFC (448.99 ± 5.02 mg GAE/g), FRAP (2.55 ± 0.40 mmol Fe2+/g) and β-carotene bleaching activity (79.49%). Whereas, non-irradiated A. bubalinum samples expressed the highest TPC (2517.07 ± 15.81 mg GAE/g) and exhibited the lowest IC50 values of α-amylase (31.99 ± 3.15 μg/ml), α-glucosidase (23.40 ± 0.69μg/ml) and pancreatic lipase (32.81 ± 7.96 μg/ml) activity. The toxicity assays also showed no significant different between irradiated and non-irradiated samples. Conclusion: The study suggests that gamma irradiation has the prospective future to increase antioxidant properties and maintaining the enzyme inhibitory activities to preserve the sample of A. bubalinum for commercial purposes.